Dialogical action research for better enterprise architecture implementation - Malta, Pedro Maia (2012)
Business-IT alignment has been studied for quite some time but it is still a key concern for IT executives. Traditional approaches may have been successful in the past, as researchers have been studying business-IT alignment concerning its impact on organizational performance or its antecedents. However, the question remains: “how to provide an easy and quick way of achieving and sustaining Business-IT alignment?” Enterprise Architecture implementation under a Business Process Management approach may be a useful way of looking into good practices to achieve and sustain business-IT alignment. This work emphasizes the adoption of Dialogical Action Research as an adequate methodology to improve theoria and praxis for a better enterprise architecture implementation. Supported on reflective one-on-one dialogues between researcher and practitioner, dialogical action research acknowledges the important role and contributions of the latter for enterprise architecture implementation when compared with the modest contributions from academia. Emerging from many years of practice, a particular praxis is under examination in this work particularly regarding the development of an organizational competences model considered as an important piece for enterprise architecture implementation. Such model fosters the discussion of the business strategy while making clear the interrelations among competences and more explicit the business model. From a dialogical action research, as work is carried out, recommendations will be issued to improve consulting praxis and inform theoria while solving real world problems in the course of enterprise architecture implementation at municipalities.